KETERAMPILAN MENULIS TEKS LAPORAN HASIL PENGAMATAN PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Lathifah, Resti; Maryono; Khoirunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Fifth grade elementary school students are still unable to write observation report texts correctly in terms of text structure and title, linguistic rules and text content, so the aim of this research is to describe the skills of writing observation report texts in terms of text structure. and title, linguistic rules, and text content for fifth grade elementary school students. This research was carried out at SDN. 80/1 Km. 3 Muara Bulian from January to May 2024. Research data was collected through assignment techniques to students (as primary data) and sending questionnaires to students. After data collection, the test findings are assessed using a skills assessment instrument to produce an observation report text, which is then summarized and divided into assessment categories. This research uses a qualitative approach and uses a case study design. Participants in this research were VB SDN class students. 80/1 km 3 Muara Bulian. Research findings show that fifth grade elementary school children have adequate writing skills based on observations. Based on the research results, it can be concluded that the report text production skills demonstrated by fifth grade elementary school children are sufficient.